Characteristics of Pain and Palliative Care in Kerala - Santha S (International Journal of Physical and Social Sciences, 2014)
Aim The main objective of the study is to study the characteristics of Pain and Palliative Care in Kerala. Materials and Methods The respondents of the study include Pain and Palliative care patients in the State of Kerala. The sample consisted of 871 patients comprising of 471 males and 400 females. The data collected were suitably classified and analyzed keeping in view the objectives of the study. For the purpose of analysis, statistical tools like averages, percentages, rank test and Pearson‟s Chi Square test were applied. Results Prescribing medicines was the major physical care provided by the doctors both to male and female patients. The major physical care provided by the nurses to male patients included „attending to the bed sore‟ and „changing clothes‟. „Giving medicines‟ was the major physical care provided by the nurses to female patients. The major physical care provided by the volunteers to male patients included „bathing‟ and „Changing clothes‟. For female patients, the major physical care given by the volunteers was „giving medicines‟. Most of the male and female patients opined that they did not require any service other than those provided by the units and said that palliative care service was absolutely essential for the society